Implementation of E-Learning-Based Islamic Religious Education - Djazilan, Muhammad Sukron; Hariani, Mila (Metromedia, 2022)
Implementation of Islamic Religious Education is an effort to instil Islamic Aqidah to students as a generation of Islam to understand, live, believe in the truth of Islamic teachings, and be willing to practice the values of Islamic teachings at all times, whenever and wherever they are. Currently, the situation and conditions faced by teachers are related to the existence, involvement and advancement of technology. There are challenges that must be faced by adapting to all aspects of life that involve technology. The educational process has involved technology and every educator must use it to assert themselves as worthy of being a conveyer of knowledge and knowledge. The Covid-19 pandemic has hampered the learning process that has been accustomed to being done face-to-face in the classroom. The emergence of online learning methods has provided the latest alternative for the learning process. The concept of online learning is a reference in rebuilding the education system that is adapted to the current era of development. This paper will describe e-learning media, implementation, effectiveness and challenges of Islamic religious education learning. Digitalization of Islamic religious education learning can be done through the application of e-learning in teaching and learning activities with the help of media to connect the results of interactions between educators and students in online-based learning spaces without being hindered by time and space.